UJI EFEK EPITELISASI EKSTRAK BATANG WOLE WOE ASAL KABUPATEN HALMAHERA TENGAH TERHADAP PENYEMBUHAN LUKA BAKAR PADA TIKUS - Safriani Rahman; Rachmat Kosman; Sitti Amirah (As-Syifaa Jurnal Farmasi, 2022)
Wole woe is a native plant of Indonesia which is widely used by the people of Central Halmahera as a medicinal plant. Empirically this plant is widely used for wound treatment. This study aims to determine the effect of epithelialization of wole woe stem extract and determine the effective concentration and duration of wound healing in rats after administration of wole woe stem extract. This research was conducted experimentally in a laboratory using 25 rats which were divided into 5 groups consisting of 1 control group, 1 comparison group, and 3 treatment groups of wole woe stem extract. Wound induction was carried out using a 100 0C hot plate measuring 2x2 cm and affixed to the surface of the rat's back skin for 2 seconds. After a burn is formed, the extract is applied 2 times a day for 21 days. Observations on wound healing were carried out macroscopically and measuring the surface area of the wound. The results showed that the administration of wole woe bark extract influenced healing second-degree burns in rats. The results of statistical analysis showed that there was no difference between the comparison group and the extract test group (p>0.05). Based on the percent reduction in wound, the most effective concentration in wound healing was 5% (99.75%). Wound healing time in rats was 21 days.